Sustainable Finance at CCAFS/Alliance: Scaling Science and Innovation to Mobilize Finance for Food Systems Transformation - Newman, Richard (2021)
Richard Newman SPECIAL EVENT Funding Food System Transformation in Developing Countries: An example from Ethiopia UNFSS Side Event -- Co-organized by IFPRI, The Alliance of Bioversity International and CIAT, CGIAR SEP 24, 2021 - 08:00 AM TO 09:30 AM EDT